Using field notes to evaluate competencies in family medicine training: a study of predictors of intention - Lacasse, Miriam; Douville, Frédéric; Desrosiers, Émilie; Côté, Luc; Turcotte, Stéphane; Légaré, France (Canadian Medical Education Journal, 2013)
Background: Documenting feedback during clinical supervision using field notes (FN) is a recommended competency-based evaluation strategy that will require changes in the culture of medical education. This study identified factors influencing the intention to adopt FN in family medicine training, using the theory of planned behaviour. Methods: This mixed-methods study involved clinical teachers (CT) and residents from two family medicine units. Main outcomes were: 1) intention (and its predictors: attitude, perceived behavioural control (PBC) and normative belief) to use FN, assessed using a 7-item Likert scale questionnaire (1: strongly disagree to 7: strongly agree) and 2) related salient beliefs, explored in focus groups three and six months after FN implementation. Results: 27 CT and 28 residents participated. Intention to use FN was 6.20±1.20 and 5.74±1.03 in CT and residents respectively. Predictors of this intention were attitude and PBC (mutually influential: p = 0.04), and normative belief (p = 0.007). Focus groups identified underlying beliefs regarding their use (perceived advantages/disadvantages and facilitators/barriers). Conclusion: Intention to adopt field notes to document competency is influenced by attitude, perceived behavioural control and normative belief. Implementation of field notes should be preceded by interventions that target the identified salient beliefs to improve this competency-based evaluation strategy.